2018
DOI: 10.1002/jobm.201800200
|View full text |Cite
|
Sign up to set email alerts
|

Physiological background of the remarkably high Cd2+ tolerance of the Aspergillus fumigatus Af293 strain

Abstract: The physiological background of the unusually high cadmium tolerance (MIC > 2 mM) of Aspergillus fumigatus Af293 was investigated. The cadmium tolerance of the tested environmental and clinical A. fumigatus strains varied over a wide range (0.25 mM < MIC < 1 mM). Only the Af293 strain showed a MIC value of >2 mM, and this phenotype was accompanied by increased in vivo virulence in mice. A strong correlation was found between the cadmium tolerance and the transcription of the pcaA gene, which encodes a putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…and Oligo Analyser (version 1.0.2) software and were purchased from Integrated DNA Technologies. Three parallel measurements were performed with each sample in a LightCycler 480 II real-time PCR instrument (Roche, Switzerland) (40). Relative transcription levels were quantified with the ΔΔCP method using the formula ΔΔCP ϭ ΔCP control Ϫ ΔCP treated , where ΔCP treated ϭ CP tested gene Ϫ CP reference gene , measured from treated cultures, and ΔCP control ϭ CP tested gene Ϫ CP reference gene , measured from control cultures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and Oligo Analyser (version 1.0.2) software and were purchased from Integrated DNA Technologies. Three parallel measurements were performed with each sample in a LightCycler 480 II real-time PCR instrument (Roche, Switzerland) (40). Relative transcription levels were quantified with the ΔΔCP method using the formula ΔΔCP ϭ ΔCP control Ϫ ΔCP treated , where ΔCP treated ϭ CP tested gene Ϫ CP reference gene , measured from treated cultures, and ΔCP control ϭ CP tested gene Ϫ CP reference gene , measured from control cultures.…”
mentioning
confidence: 99%
“…Only data calculated with the ACT1 (CPAR2_201570) transcription values are presented. ΔΔCP values are expressed as means Ϯ SD calculated from three independent measurements, and ΔΔCP values significantly (P Ͻ 0.05) higher or lower than zero were determined using Student's t test (40).…”
mentioning
confidence: 99%
“…2017 ). Not surprisingly, the Kruskal-Wallis test did not show any significant difference in the cadmium tolerance among the Aspergillus species possessing two, one or even zero pcaA orthologs ( Kurucz et al. 2018b ).…”
Section: Discussionmentioning
confidence: 94%
“…2018b ). Moreover, the MIC 50,cd values of 10 A. fumigatus isolates varied within a wide range (0.25 mM–>2 mM) and showed strong positive correlation with the relative transcription of the pcaA gene ( Kurucz et al. 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the previous study used different genetic backgrounds compared to the current study: deletion of argB was performed in a derivative of A. fumigatus Af293 [19][20][21], which might indicate that the genetic background interferes with the effect of arginine auxotrophy on virulence in the G. mellonella model. In this context, it is interesting to note that several studies revealed significant differences in physiological responses to abiotic stimuli and virulence in murine models of invasive pulmonary aspergillosis between A. fumigatus Af293 and other A. fumigatus isolates including commonly used A. fumigatus CEA10 [44][45][46][47][48]. Sugui et al [47] concluded that Af293 possesses a nutritional deficiency.…”
Section: Discussionmentioning
confidence: 99%